Declarative memory affects procedural memory: The role of semantic association and sequence matching. (July 2019) - Xie, Ting-Ting; Wang, Tian-Ze; Wei, Yi-Ping; Ye, En-Cheng
Abstract: Declarative memory and procedural memory have their own independent information processing channels, but also share common processing mechanisms. Converging evidence recently shows that declarative learning can inhibit the performance of procedural memory. However, other studies also show that there may be semantic association effect and sequence expectation effect. We assumed that this interference effect of declarative memory on procedural memory could vanish or even be transformed into the enhancing effect when there was semantic association or both semantic association and sequence matching existed between two tasks. Experiment 1 examined the role of semantic association in the influence of declarative memory on procedural memory. We found that the performance of the semantic association group was significantly better than that of the baseline group, while the performance of the semantic independent group was significantly worse than that of the baseline group. In Experiment 2, based on semantic association, the role of sequence matching in the impact of declarative memory on procedural memory was tested. As a result, the accuracy of the sequence matching group was significantly higher than that of the baseline group, while the accuracy of the sequence mismatched group was not significantly different from that of the baseline group. The results of the two experiments suggest that the effect of declarative memory on procedural memory is not a fixed relationship. It is modulated by semantic association and sequence matching between two tasks. Declarative memory can interfere with procedural memory when two tasks have no semantic association, however, when there is semantic association the interference effect can vanish. Further, when both semantic association and sequence matching exist, the interference effect can be reversed into an enhancing effect. Highlights: Converging evidence recently shows that declarative learning can inhibit the performance of procedural memory. But we found that the influence of declarative memory on procedural memory is not a fixed relationship. Performing declarative and procedural memory tasks one after another can give rise to interference, but the semantic association between them can make this interference vanished. If there are both semantic association and sequence matching between declarative memory and procedural memory, an enhancing effect will be observed.